How can LMS affect student’s motivation and engagement? - Ferreira, R.; Cardoso, E.; Oliveira, J. (Digital technologies and transformation in business, industry and organizations, 2023)
Technology has revolutionized the education system. Many tools such as Learning Management Systems (LMS) were developed to enhance the learning process. With this new technology, teachers and universities can explore options otherwise difficult to implement. Keeping students engaged is one of the biggest challenges that educational institutions face. Students’ motivation, engagement, and performance can be affected by using LMS. Strategies like self-regulated learning, gamification, and real-time at-risk student detection can be more easily implemented. The analysis of the effects of LMS on learning is made in form of a systematic literature review (SLR). 33 studies published after 2017 were extracted for full-text analysis.